Analisis faktor-faktor yang mempengaruhi kinerja keuangan (studi kasus pada bank umum syariah yang terdaftar di otoritas jasa keuangan periode 2015-2019) - Marlina, Indah; Suhono, Suhono (Jurnal Riset Pendidikan Ekonomi, 2021)
This study aims to determine the factors that can affect accounting performance. The population in the study was 14 with the sample in this study were 7 Islamic Commercial Banks. The sampling technique was purposive sampling. The results of the study stated that CAR had no effect on ROA. FDR has a negative effect on ROA and BOPO has a negative effect on ROA. Data processing using SPSS V.21